2009
DOI: 10.1002/wnan.39
|View full text |Cite
|
Sign up to set email alerts
|

Nanofibrous composites for tissue engineering applications

Abstract: Development of artificial matrices for tissue engineering is a crucial area of research in the field of regenerative medicine. Successful tissue scaffolds, in analogy with the natural mammalian extracellular matrix (ECM), are multi-component, fibrous, and on the nanoscale. In addition, to this key morphology, artificial scaffolds must have mechanical, chemical, surface, and electrical properties that match the ECM or basement membrane of the specific tissue desired. In particular, these material properties may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 157 publications
1
42
0
1
Order By: Relevance
“…Electrospun biomaterial (silk, lactic acid and glycolic acid polymers) (Zhang et al, 2009;McCullen et al, 2009) ↓ Mechanical stability, tensile strength, elasticity …”
Section: Integrin Ligandsmentioning
confidence: 99%
See 2 more Smart Citations
“…Electrospun biomaterial (silk, lactic acid and glycolic acid polymers) (Zhang et al, 2009;McCullen et al, 2009) ↓ Mechanical stability, tensile strength, elasticity …”
Section: Integrin Ligandsmentioning
confidence: 99%
“…In this respect, synthetic matrices have been developed that feature defined and tunable compositions, organization, mechanics and ECM remodeling capabilities. Indeed, in response to this need there has been literally an explosion of publications describing the generation and application of synthetic ECMs for tissue regeneration, and the reader is referred to some excellent reviews on these topics (Ayres et al, 2009;Dutta and Dutta, 2009;Lutolf and Hubbell, 2005;McCullen et al, 2009;Rosso et al, 2005;Zisch et al, 2003). One example is given by polyethylene glycol (PEG) hydrogels -frequently used biologically compatible synthetic matrices that support cell adhesion, viability and growth (Lutolf and Hubbell, 2005).…”
Section: Tumors -A Tough Situationmentioning
confidence: 99%
See 1 more Smart Citation
“…ECM is composed of several fibrous macromolecules with a length/thickness ratio greater than 100. The diameter of these macromolecules is about 500 nm [49]. Thus electrospun nanofibers can be used to prepare similar-sized scaffolds.…”
Section: Electrospinning Methodsmentioning
confidence: 99%
“…24 Tissue engineering products are constructed from a variety of materials (eg, polymers, ceramics, and metals) for the purpose of mimicking the ECM to improve wound healing, but these products can elicit unwanted inflammatory or immune responses that lead to fibrogenic development. 25,26 With the expected impairment that results from scarring, researchers have examined using anti-inflammatory therapies or anti-TGF-b medications as preventive measures to deter fibrosis formation. It has been found that scarring effects from TGF-b1 secretion can be prevented in injured tissues through multiple methods, including blocking the actual TGF-b ligand; blocking the TGF-b receptors, which interferes with downstream signaling; or selectively inhibiting coactivators of TGF-b that lead to scar tissue formation.…”
Section: Conflict Of Interestmentioning
confidence: 99%